(3EQTGO GdYbd GdSdje Edi eRGjG GdcJGH GdcQjes - (3GdYeGOj, nCoHh GdoqSoYhO, eMeO Hf eMeO Hf eUWai, J (B982(3g`s
(3ChdgG (B:s
(3HYO GdHSedI SHMGf ef CQSd QShdg HGdgOi CeG HYO ajbhd CHh GdSYhO Hf eMeO GdYeGOj fGhjG Cf CSejg EQTGO GdYbd GdSdje Edi eRGjG GdcJGH GdcQjes
(3BNQgG (B:s
(3dGfg bGje aj XdeI GdcaQ hGdeDef bGFe aj fhQ GdESdGe hef jchf aj XdeI GdHjJ agh jQi def cGf bGFeG aj VhA GdbeQ hGdPj jchf bGFeG aj VhA GdbeQ dG jQi def jchf aj XdeJ GdHjJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 59s
(3eYLe GdeDdajf (B3 / 693s
(3cTa GdXfhf (B1 / 65s
(3TPQGJ GdPgH (B8 / 398s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs